Ascaris lumbricoides: A Rare Cause of Gastric Perforation with Intraperitoneal Migration in Pediatric Patient with Systematic Review of Literature - Khare, Atul K.; Baindur, Aditya J.; Sharma, Pramila; Chopra, Ashok K.; Singh, Kirti (Journal of Gastrointestinal Infections, 2025)
Ascaris lumbricoides is one of the most common helminthic infections globally, mainly prevalent in tropical and subtropical developing countries with poor hygiene and sanitation. Though rare, intestinal perforation can occur due to clumping up of worms, causing partial or complete obstruction, eventually leading to bowel wall necrosis and perforation. We report a case of a 14-year-old boy from rural North India, who presented with abdominal pain, vomiting, abdominal distension, and anemia for 5 days. An immediate exploratory laparotomy was done, and an enterotomy was performed to remove the worm masses. Gastric perforation was found and repaired, and a loop ileostomy was performed. The majority of intestinal obstructions due to ascariasis are managed conservatively. However, in case of complications like perforation, early surgery is required to reduce morbidity and mortality. Ascariasis remains a global health challenge. Prevention through health education and awareness programs is essential, especially in the endemic areas. Improvements in sanitation, periodic deworming, and early diagnosis are crucial. In cases with complicated presentations like perforation peritonitis, timely surgery is lifesaving.
Keywords: albendazole; ascariasis; intraperitoneal migration; parasitic infection; perforation peritonitis